Value, Strengths, and Challenges of e-Learning Modules Paired with the Flipped Classroom for Graduate Medical Education: A Survey from the National Neonatology Curriculum - Gray, Megan M.; Dadiz, Rita; Izatt, Susan; Gillam-Krakauer, Maria; Carbajal, Melissa M.; Falck, Alison J.; Bonachea, Elizabeth M.; Johnston, Lindsay C.; Karpen, Heidi; Vasquez, Margarita M.; Chess, Patricia R.; French, Heather (American Journal of Perinatology, 2020)
Objective This study aimed to determine the value, strengths, and challenges of implementing an e-learning based flipped classroom (FC) educational modality as part of the standardized physiology National Neonatology Curriculum (NNC), created for neonatal-perinatal medicine (NPM) fellow learners and faculty educators.Study Design This is a cross-sectional study of NPM fellows and faculty educators who utilized at least one of the e-learning based NNC FC respiratory physiology programs between May and September 2018. Participants were surveyed anonymously regarding their experiences participating in the NNC, including measures of preparation time. A combination of descriptive statistics and proportion comparisons were used for data analysis.Results Among 172 respondents, the majority of fellow and faculty respondents reported positive attitudes toward the educational content and case discussions, and the majority supported national standardization of NPM physiology education (92%). Fellows reported greater preclass preparation for their FC compared with previous didactic lectures (30–60 vs. 0–15 minutes, p < 0.01). Faculty facilitators reported less preparation time before facilitating a FC compared with the time required for creating a new didactic lecture (median: 60 vs. 240 minutes, p < 0.01). Both fellows and faculty respondents preferred the FC approach to traditional didactics, with fellows showing a greater degree of preference than faculty (68 vs. 52%, respectively, p = 0.04).Conclusion Fellows and faculty educators supported the FC learning, reporting peer-to-peer learning, and the establishment of a learning community which promotes adult learning and critical thinking skills. A national physiology curriculum creates equitable and engaging educational experiences for all NPM fellows while reducing individual program burden of content creation. Our findings further supported the development of an NNC using a flipped classroom modality.
Keywords: flipped classroom; graduate medical education; adult learning; curriculum design; e-learning